2018
DOI: 10.1016/j.ehj.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical role of serum Copeptin in acute coronary syndrome

Abstract: ObjectiveTo assess the role of Copeptin in diagnosis of acute myocardial infarction in troponin-blind period.Subjects and methodsThis study was conducted on 40 patients who presented to emergency department complaining of chest pain and were highly suspicious to have acute cardiac ischemia, in addition to 10 subjects serving as a healthy control group. Blood samples were collected for determination of CK-MB, cTnI and Copeptin. These were measured twice (in patients’ group); at 3 h and then at 6–9 h from admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Early identification of patients at high risk for AMI using biomarkers can guide more individualized treatment strategies. Serum copeptin can be used as a diagnostic biomarker for AMI, 15 - 18 but previous studies used different measurement timings. 23 Therefore, this study aimed to determine the time course of serum copeptin levels and investigate the correlation between serum copeptin and LV global function in a pig AMI model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Early identification of patients at high risk for AMI using biomarkers can guide more individualized treatment strategies. Serum copeptin can be used as a diagnostic biomarker for AMI, 15 - 18 but previous studies used different measurement timings. 23 Therefore, this study aimed to determine the time course of serum copeptin levels and investigate the correlation between serum copeptin and LV global function in a pig AMI model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that copeptin levels can be used for the diagnosis of AMI, 15 - 18 , 23 , 27 but they all used different measurement time points and the best time point still needs to be defined. In addition, because of the variations in methods and patients among studies, no direct comparisons among studies are possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu çalışmalardan amaç hastalık ile ilgili daha erken ipuçları bularak erken tanı konulması ve erken tedaviye başlanmasıdır. Hatta en ideal amaç tanı koymadan önceki aşamada bu hastalığın gelişme riskinin hesaplanması ve riski fazla olan bireylerde hastalık gelişimini önlemeye yönelik önlemlerin alınmasıdır (Abd El Baky Mahmoud, Shaaban, & Ali Ramzy, 2018;Li et al, 2018;Tang & Zhou, 2019).…”
Section: Discussionunclassified